Evolution of Antibiotic Tolerance Shapes Resistance Development in Chronic Pseudomonas aeruginosa Infections - Isabella Santi (American Society for Microbiology, 2021)
Over the past decades, pan-resistant strains of major bacterial pathogens have emerged and have rendered clinically available antibiotics ineffective, putting at risk many of the major achievements of modern medicine, including surgery, cancer therapy, and organ transplantation. A thorough understanding of processes leading to the development of antibiotic resistance in human patients is thus urgently needed.